Post a New Question

math

posted by .

Input 1 2 4 5 10 12
Output 3 5 9 11 21 25
Write the rule

  • math -

    1 3
    2 5
    3 try constant difference of 2 -->7
    4 9
    5 11
    6 -->13
    7 -->15
    8 -->17
    9 -->19
    10 21
    11 --> 23
    12 25 so it worked
    accordind to my rule
    0 1
    so
    y(n) = 2 + y(n-1)
    or y(n) = 1 + 2(n)
    y = 2 n + 1

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

More Related Questions

Post a New Question